Generate Beaufort Cipher Key Based on Blum-Blum Shub For Secure Digital Image - Ndruru, Eferoni (Bahasa Indonesia, 2021)
Data security is not only due to the complexity of the algorithms used, but one of the most important factors is the security of the keys used. One of the most popular data that needs to be backed up today is digital images. However, these days, the algorithms used to back up data are often attacked. This is because the structure of the key formations used is still weak. One of the data security algorithms that form a simple key is the Beaufort cipher. It relies on the duplication of key characters to form the key for each protected element. Key generators based on blum-blum shub technology can generate very random and difficult-to-guess keys, so the strength of the keys you use can enhance the resilience of protected data. Keys generated based on blum-blum shub technology will later be used in the process of encrypting and decrypting pixel values ​​in digital images.